Isolamento de uma quitinase extraída do cefalotórax do camarão marinho Litopenaeus schmitti (BURKENROAD, 1936) : avaliação de suas atividades antimicrobiana e larvicida - Godone, Roberta Luciana do Nascimento (2011)
Chitinases are enzymes involved in degradation of chitin and are present in a range of organisms, including those that do not contain chitin, such as bacteria, viruses, plants and animals, and play important physiological and ecological roles. Chitin is hydrolyzed by a chitinolytic system classified as: endo-chitinases, exo-chitinases and N-acetyl-b-D-glucosaminidases. In this study a Litochitinase1 extracted from the cephalotorax of the shrimp Litopenaeus Schmitt was purified 987.32 times using ionexchange chromatography DEAE-Biogel and molecular exclusion Sephacryl S-200. These enzyme presented a molecular mass of about 28.5 kDa. The results, after kinetic assay with the Litochitinase1 using as substrate p-nitrophenyl-N-acetyl-b-Dglucosaminideo, showed apparent Km of 0.51 mM, optimal activity at pH ranging from 5.0 to 6.0, optimum temperature at 55°C and stability when pre-incubated at temperatures of 25, 37, 45, 50 and 55°C. The enzyme showed a range of stability at pH 4.0 to 5.5. HgCl2 inhibited Litochitinase1 while MgCl2 enhances its activity. Antimicrobial tests showed that Litochitinase1 present activity against gram-negative bacterium Escherichia coli in the 800 μg/mL concentration. The larvicidal activity against Aedes aegypti was investigated using crude extracts, F-III (50-80%) and Litochitinase1 at 24 and 48 hours. The results showed larvicidal activity in all these samples with EC50 values of 6.59 mg/mL for crude extract, 5.36 mg/mL for F-III and 0.71 mg/mL for Litochitinase1 at 24 hours and 3.22 and 0.49 mg/mL for the F-III and Litochitinase1 at 48 hours, respectively. Other experiments confirmed the presence of chitin in the midgut of Aedes aegypti larvae, which may be suffering the action of Litochitinase1 killing the larvae, but also the absence of contaminating proteins as serine proteinase inhibitors and lectins in the crude extract, F-III and Litochitinase1, indicating that the death of the larvae is by action of the Litochitinase1. We also observed that the enzymes extracted from intestinal homogenate of the larvae no have activity on Litochitinase1. These results indicate that the enzyme can be used as an alternative to control of infections caused by Escherichia coli and reducing the infestation of the mosquito vector of dengue.